Influence of pressure in vacuum drying chamber on shrinkage of defrosted strawberries - Piotrowski, Dariusz; Ignaczak, Marcin (Wpływ ciśnienia w komorze suszarki próżniowej na skurcz rozmrożonych wysuszonych truskawek, 2018)
The material were raw or defrosted strawberries of Senga Sengana variety with the diameter of 26-30 mm. Fruits were dried for 16 hours at the temperature of 60°C under constant or variable conditions considering level of pressure. Pressure during the drying process was on a fixed level of: 5, 10 and 15 kPa or a change of pressure was introduced among extreme values. Shrinkage of strawberries was examined with the use of two methods: the volumetric method and measurement of linear dimensions in horizontal and vertical space. Shrinkage obtained under the fixed pressure level was greater for higher values in the drying chamber. Horizontal linear shrinkage of dried fruit was always lower than vertical linear shrinkage. For dried strawberries volumetric shrinkage obtained for defrosted fruits after vacuum drying under variable pressures did not reveal clear differences between respective values of shrinkage. The lowest level of pressure (5 kPa), applied in any phase of vacuum drying under variable pressure, caused a shrinkage decrease in comparison to drying shrinkage after processes under other fixed pressure
Nauki Inżynierskie i Technologie = Engineering Sciences and Technologies, 2018, Nr 3 (30), s. 49-61
Keywords: shrinkage; vacuum; drying; constant and variable conditions; pressure; moisture content; dried strawberries; skurcz; suszenie próżniowe; stałe i zmienne warunki; ciśnienie; zawartość wilgoci; suszone truskawki